CHALLANGES FACING THE EMERGING ECONOMY DURING COVID-19 THE CASE OF JORDAN - Al-Lozi , Basem; Hamed, Sheren (European Journal of Business and Strategic Management, 2021)
Purpose: The purpose of this study was to explore the challenges of the Jordanian economy during COVID-19. The Jordanian economy may have to face different scenarios in his macro-environment. Specifically, the study focused on the impact COVID-19 on the Jordanian economy. Methodology: An exploratory research method was used to build three scenarios. The sample randomly selected from Jordanians in the capital of Jordan Amman. The study divided the sample to three groups and asking them three questions related to the expectations of the impact of COVID-19 on the Jordanian economy for the coming years. Results: The study findings revealed that the majority of respondents (55.2%) are optimistic that the COVID-19 will finish and Jordan economy will be booming. Unique contribution to theory, practice and policy: Recommendations were provided for Jordanian policy makers to deal scenarios. For example Jordan government and policy makers has to be pragmatic, and work toward lowering level of expectations among Jordanian economy to avoid the negative impact of COVID-19 on the economy. Cooperation between the public sector and private sector in implementing the instructions of the World Health Organization and the Ministry of Health to decrease the number of cases to open more sectors which will have a positive impact on the Jordanian economy.